2023
DOI: 10.18488/61.v11i3.3380
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based learning utilizing assistive virtual simulation in mobile application to improve students’ critical thinking skills

Abstract: In a distance learning system, students tend to feel bored and their learning motivation decreases which makes an impact on their critical thinking (CT) being undeveloped. A motivating digital pedagogical infrastructure is needed to empower students' CT skills. The current study aimed at intervening Problem Based Learning (PBL) with PhET (Physics Education Technology) assistive virtual simulation in mobile application and evaluating its impact on students' CT skills. Experimental design (randomized pretest-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…By summing up individual scores on the CT test, the cumulative performance of each student's CT skills was determined. This follows the principles of previous studies (Prayogi et al, 2018;Suhirman & Prayogi, 2023).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…By summing up individual scores on the CT test, the cumulative performance of each student's CT skills was determined. This follows the principles of previous studies (Prayogi et al, 2018;Suhirman & Prayogi, 2023).…”
Section: Discussionmentioning
confidence: 70%
“…The purpose of this approach is to enhance students' Critical Thinking (CT) abilities. The PBL approach for this study adheres to the guidelines outlined by Suhirman and Prayogi (2023) The adaptability of problem-based learning (PBL) makes it compatible with mobile applications. Previous research has demonstrated that employing mobile PBL applications can effectively enhance students' CT abilities (Ismail et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assistive technology in science, initially designed to meet and facilitate access to the learning rights of students with disabilities (Smith, 2021), has evolved into a learning visualization instrument alongside the progress of simulation technology. It is now recognized as assistive virtual simulation (Suhirman & Prayogi, 2023). Virtual technology has been studied and can be beneficial in terms of accessibility (simplifying the learning process) (Zhang et al, 2021), motivating students in learning (Ismail, 2022), and serving as a digital learning bridge to comprehend abstract concepts (Verawati et al, 2022).…”
Section: Axiology Of Technology-based Future Science Educationmentioning
confidence: 99%